Outcomes of Limberg flap repair in recurrent pilonidal sinus disease: a study in a district hospital of Bangladesh - Rajib, M. Minhaz Uddin; Afroz, Most Masuda; Islam, M. Mahinul; Rahman, Karina; Ahmed, Tania (International Surgery Journal, 2024)
Background: Pilonidal sinus disease (PSD) is a chronic condition affecting the sacrococcygeal region, often seen in young adults. Numerous surgical techniques have been documented in medical literature for its treatment. This study aimed to evaluate the outcomes of the Limberg flap repair (LFR) in recurrent pilonidal sinus disease. Methods: This prospective observational study was conducted in the General Hospital, Nilphamari, Bangladesh from January 2021 to December 2022. The study included 47 cases of recurrent PSD scheduled for LFR, selected through purposive sampling. Data analysis was conducted using Microsoft office tools. Results: In the analysis of outcomes, the study found the following mean±SD values: operation duration of 53.4±7.2 minutes, first mobilization at 1.1±0.2 days, work incapacity for 7.3±1.5 days, pain visual analog score (VAS) score of 1.7±0.3, complete healing in 21.7±7.9 days, and painless toilet seating achieved in 1.2±0.6 days for all participants. Postoperative complications included seroma (8.5%) and hematoma (6.4%) in more than 5% of participants. Most patients achieved excellent results (62%), followed by 21% with good and 17% with fair outcomes. Conclusions: LFR stands out as an effective and safe treatment option for recurrent PSD. It offers advantages such as reduced complication rates, shorter hospital stays, quicker return to work, minimal pain, and high patient satisfaction.